2017
DOI: 10.1111/iju.13500
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of indwelling metallic stents for malignant extrinsic ureteral obstruction

Abstract: Metallic stents are excellent in maintaining patency compared with the conventional stents. Therefore, they can be used as first-line treatment of malignant ureteral obstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…In our previous study evaluating the treatment outcomes of indwelling metallic stents for malignant extrinsic ureteric obstruction, we reported a patency rate of 86.0% at 6 months and 60.0% at 1 year among 52 patients (66 ureters) 14. Our current retrospective analysis follows up on these initial findings, demonstrating the possible superiority of metallic stents over polymeric stents for the treatment of MUO.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In our previous study evaluating the treatment outcomes of indwelling metallic stents for malignant extrinsic ureteric obstruction, we reported a patency rate of 86.0% at 6 months and 60.0% at 1 year among 52 patients (66 ureters) 14. Our current retrospective analysis follows up on these initial findings, demonstrating the possible superiority of metallic stents over polymeric stents for the treatment of MUO.…”
Section: Discussionsupporting
confidence: 51%
“…In patients with metallic stents indwelled, there were a number of cases of bilateral ureteral obstruction due to gastrointestinal cancer, which may have influenced this outcome. We previously reported that the rate of bilateral obstruction was significantly higher than the rate of unilateral obstruction 14. Moreover, metallic stents have an anticipated indwelling period of 1 year compared to 3–6 months for polymeric stents.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, a metallic stent was approved and used clinically for the treatment of ureteral obstruction [ 3 ]. The metallic stent is tough due to its spiral shape and the hard material from which it is constructed, and can therefore be left in place for a longer period.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is usually first treated by the implantation of a single J stent by a retrograde approach; however, the stent is sometimes bent due to anatomic reasons, necessitating nephrostomy. The Resonance® metal stent is a continuous, unfenestrated, all-metal, double-pigtail ureteric stent with no end or side holes [ 3 , 4 ]. We herein report the first case of a patient with ureteral stricture after radial cystectomy with the creation of an ileal conduit who was successfully treated by the insertion of a metal stent with a combined antegrade and retrograde approach.…”
Section: Introductionmentioning
confidence: 99%